Pengaruh Bimbingan Karier terhadap Efikasi Diri dalam Pengambilan Keputusan Karier pada Siswa - Dyan Widianingrum; Thomas Dicky Hastjarjo (Faculty of Psychology, Universitas Gadjah Mada, 2016)
This study aimed to determine the effect of career guidance on the self-efficacy in career decision-making with mastery goal orientation as co-variables. The research design used quasi experiment consisting of two groups: the experimental group and the control group. The experimental group received treatment (career guidance). Self-efficacy in career decision-making was measured using the questionnaire of self-efficacy in career decision-making and mastery goal orientation was measured with a scale of mastery goal orientation. Career guidance module was administered to the experimental group. Subjects in this study amounted to 48 students a class XI of SMA X in Yogyakarta. Analysis of covariance was used to analyse the data and resulted in no relationship between mastery goal orientation and self-efficacy in career decision making (p>.05). Therefore the analysis turned to mixed anova resulting that there was the effects of the career guidance to self efficacy in career decision making (F=104.074; p<0.05).